(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2025)
This paper examines the textual variants between the 1947 edition of Sibilla Aleramo’s novel Amo, dunque sono and its first edition, published in 1927. A comparison of the two editions reveals a process of abridgement and omission, to which Franco Matacotta – Aleramo’s partner at the time – also contributed. The result is an edition not only less substantial, but also revised to eliminate stylistic and thematic elements considered unsuitable for the new post-war cultural and political climate.